ANALISIS POSISI MATAHARI PADA SISTEM ZODIAK MODERN BERDASARKAN PERSPEKTIF ILMU FALAK - Awalia, Fatima Restu; Aisyah, Nur A (Universitas Islam Negeri Alauddin Makassar, 2026)
Abstract The modern zodiac system originated from the division of the Sun's annual apparent path along the ecliptic and was initially developed as an astronomical coordinate system. Over time, however, it has become more widely associated with astrology, linking the Sun's position to human personality traits, while its correspondence with actual astronomical conditions remains a subject of debate. This study aims to analyze the Sun's position within the modern zodiac system based on falakiyah data and to examine the modern zodiac from the perspective of Ilmu Falak (Islamic astronomy). This research employs a qualitative approach using a library research method. Data were collected through a literature review of books, scholarly journal articles, and astronomical references related to the Sun's position, the zodiac system, and the phenomenon of the precession of the equinoxes. Data were analyzed using a descriptive-analytical approach through the stages of data reduction, classification, interpretation, and conclusion drawing. The findings reveal that the modern zodiac system no longer fully represents the Sun's actual position relative to the zodiac constellations due to the gradual shift of the vernal equinox caused by the precession of the equinoxes. Furthermore, the analysis based on falakiyah data demonstrates that the Sun's position can be accurately determined through hisab (astronomical calculation) and modern astronomical data, providing a more objective representation of the Sun's annual apparent motion along the ecliptic. This study concludes that Ilmu Falak offers a scientific framework for evaluating the modern zodiac system based on verified astronomical data while emphasizing the distinction between the zodiac as an astronomical coordinate system and astrology as a form of symbolic interpretation. The implications of this study are expected to strengthen the development of Ilmu Falak through the application of modern astronomical data and to serve as a scientific reference for distinguishing empirically verifiable astronomical concepts from symbolic astrological interpretations. Keywords: Ilmu Falak, Sun Position, Modern Zodiac, Falakiyah Data, Precession of the Equinoxes.